Flexibility of Rejang Semendo System in Modern Marriage Law: An Islamic‑Law Analysis - Shesa, Laras; Jalaluddin, Jalaluddin; Yuniardi, Harry; Kholid, Muhamad; Utami, Henny Septia (IAIN Manado, 2025)
The Semendo constitute an indigenous ethnic group in South Sumatra, Indonesia. This research aims to analyze the flexibility of the Semendo system in Rejang customary law and its conformity with the principles of Islamic law, particularly within the framework of maqāṣid al-syarī'ah. This study employs a normative-juridical method, utilizing a conceptual and comparative approach to analyze customary norms, Islamic legal principles, and national marriage law provisions. The findings indicate that the Semendo system, particularly the Semendo Rajo-Rajo model, demonstrates a significant accommodating character towards the values of justice, equality of rights, and the protection of property and lineage, which are integral parts of maqāṣid al-syarī'ah. Its flexibility allows it to function as a contextual and adaptive alternative model of marriage law. In conclusion, the integration of customary law values and Islamic law in the Semendo system provides a strong foundation for a more inclusive and culturally rooted reformulation of national marriage law in Indonesia. This study contributes to the scientific discourse by offering a methodological framework for harmonizing local wisdom with Islamic legal principles, which can be applied to the study of other customary law systems across the archipelago. Furthermore, it provides an academic foundation for the future development of a more pluralistic and context-sensitive national marriage law.